Optimization of Teak Leaf Extract (Tectona grandis L.F) and Carbopol in Hair Dye Formulation Using Factorial Design Method - halimah, Sofiati; Rosanti, Afi Sania; Dwiningrum, Riza; Pratiwi, Mida (LPPM Universitas Dhyana Pura, 2025)
Cosmetics are preparations intended for use on the external parts of the human body, and one commonly used type is hair dye. However, many hair dye products on the market still rely on synthetic dyes, which may pose health risks such as irritation or internal organ damage if used long-term. To reduce these risks, the use of natural dyes has become an increasingly popular alternative, especially due to their content of anthocyanins that can provide natural color. One such natural ingredient is teak leaves (Tectona grandis L.F), which are rich in anthocyanin pigments and other bioactive compounds. This study aims to determine the optimal hair dye gel formulation using a combination of teak leaf extract and Carbopol, utilizing the Factorial Design method. The research was conducted observationally by preparing several formulas with varying concentrations, followed by evaluating the physical properties of each formulation, including organoleptic tests, pH, homogeneity, spreadability, adhesion, viscosity, and protective ability. The results indicated that the optimal formula consisted of 15% teak leaf extract and 2% Carbopol, showing a pH of 6.1±0.80, adhesion time of 7.74±2.41 seconds, spreadability of 6.43±0.60 cm, and viscosity of 34,000±12,124 cps. The resulting gel appeared stable, homogeneous, and capable of protecting the scalp. Therefore, the combination of teak leaf extract and Carbopol can be formulated into a natural hair dye cosmetic product that meets quality standards, offers good stability, and is safe for use.